2001
DOI: 10.1002/gcc.1206
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic clues to breast carcinogenesis

Abstract: The somatic mutation theory of cancer maintains that tumorigenesis is driven by genetic alterations, many of which are visible cytogenetically. We have examined breast cancer by chromosome banding analysis after short-term culturing of tumor cells and here review our findings in 322 karyotypically abnormal samples obtained since 1992 from 256 patients. The screening capabilities of this technique enabled us to identify several cytogenetic subgroups of breast cancer, to study the intratumor heterogeneity of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 87 publications
4
51
1
Order By: Relevance
“…3,4 Gains of the long arm of chromosome 1 and losses of chromosome 16q are often the result of unbalanced translocations between these two chromosomes: 1,6 less frequently, they are the result of other rearrangements. 2,5 Chromosome 1q gains and 16q losses are considered as early changes since they have been detected as the sole chromosome abnormalities in near-diploid breast carcinoma 1,6 and in well-differentiated samples with a few alterations. 3,7 These genetic changes and the resulting chromosome imbalances have been thought to play a pathogenic role in breast carcinoma development.…”
mentioning
confidence: 99%
“…3,4 Gains of the long arm of chromosome 1 and losses of chromosome 16q are often the result of unbalanced translocations between these two chromosomes: 1,6 less frequently, they are the result of other rearrangements. 2,5 Chromosome 1q gains and 16q losses are considered as early changes since they have been detected as the sole chromosome abnormalities in near-diploid breast carcinoma 1,6 and in well-differentiated samples with a few alterations. 3,7 These genetic changes and the resulting chromosome imbalances have been thought to play a pathogenic role in breast carcinoma development.…”
mentioning
confidence: 99%
“…This chromosome is one of the most frequently affected in breast cancers (Dutrillaux et al, 1990;Bièche et al, 1993;Pandis et al, 1995;Teixeira et al, 2002; http://cgap.nci.nih.gov/Chromosomes/ RecurrentAberrations). Analyses of breast tumours have established a frequency of breaks as follows: 1p36 (6.5%), 1p22 (6.1%), 1p13 (5.9%), 1q10 (24%), 1q11 -12 (7%), 1q21 (9.1%), 1q25 (5%) and 1q42 (5.9%) (Teixeira et al, 2002). Frequent allelic imbalances have been found at 1p36 (11%), 1q42 -44 (13 -14%) and amplification is commonly observed at 1q21.…”
Section: Comparison Of Our Results With Literature Datamentioning
confidence: 99%
“…As opposed to chromosome 1, aberrations of chromosome 5 are relatively rare in breast cancers (http://cgap.nci.nih.gov/Chromosomes/RecurrentAberrations); they target preferentially the 5p15 region (Teixeira et al, 2002). Allelic imbalances have been reported with gains of 5p in 39% of breast tumour cell lines (Forozan et al, 2000).…”
Section: Comparison Of Our Results With Literature Datamentioning
confidence: 99%
“…Also, it occurs usually as the sole clonal abnormality and in benign proliferative disease of the breast. Molecular studies have confirmed loss of 3p in breast cancers, with loss at 3p13 -14 having been reported in more than 40% of breast carcinomas (Teixeira et al, 2002). 'A candidate tumour suppressor gene in this region is FHIT and some studies have shown that this gene is involved in breast cancery'.…”
Section: Breast Cancermentioning
confidence: 97%
“…The cytogenetics of breast cancer has recently been reviewed for 322 karyotypically abnormal samples from 256 patients (Teixeira et al, 2002). 'Interstitial deletions of the short arm of chromosome 3, with 3p14 as a minimally common deleted region, were described as a recurrent change in breast carcinoma by Pandis et aly.…”
Section: Breast Cancermentioning
confidence: 99%